ChemInform Abstract: Stereoselective Synthesis and Reactions of Secondary Alkyllithium Reagents Functionalized at the 3‐Position. Issue 27 (18th June 2015) - Moriya, Kohei; Didier, Dorian; Simon, Meike; Hammann, Jeffrey M.; Berionni, Guillaume; Karaghiosoff, Konstantin; Zipse, Hendrik; Mayr, Herbert; Knochel, Paul
Abstract It is demonstrated that 3‐Tbs‐oxy‐substituted alkyllithium compounds can be generated in a stereoconvergent manner from the corresponding iodo‐compounds.